MEDIA TECHNOLOGIES AS A FACTOR OF ORGANIZATIONAL AND TECHNOLOGICAL CHANGES OF HIGH SCHOOL LIBRARIES - Kyslyuk, Liubov (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The multimedia technologies as a factor of organizational and technological changes in the high school libraries had been considered. The directions of learning of the multimedia technologies in the high school libraries of Ukraine have been analyze